Triglyceride–glucose index as a prognostic marker of endovascular thrombectomy in patients with ischemic stroke: a retrospective study - Sun, Zhaoliang; Meng, Xuchen; Mei, Zixian; Deng, Tanjun; Lv, Xin; Xiao, Jiexi; Zhu, Lin; Tang, Dingzhong; Zhong, Weijie; Li, Yi (Frontiers in Medicine, 2025)
ObjectiveThis study investigates the association between the triglyceride–glucose (TyG) index, a surrogate marker for insulin resistance, and clinical outcomes in patients with acute ischemic stroke (AIS) after endovascular thrombectomy (EVT).MethodsThis retrospective study included 179 patients with AIS who underwent EVT. The TyG index was calculated as ln[triglycerides (TGs) (mg/dL) × glucose (mg/dL)/2] from admission blood samples. The primary outcome was functional status at 90 days post-stroke, assessed by the modified Rankin Scale (mRS). A multivariate logistic regression analysis was performed to evaluate the association between the TyG index and outcomes after adjusting for potential confounders.ResultsAmong the 179 patients, 77 (43.0%) had favorable outcomes (mRS ≤ 2) and 102 (57.0%) had poor outcomes (mRS > 2) at 90 days post-stroke. The TyG index was significantly higher in the poor outcome group compared to the favorable outcome group. The receiver operating characteristic curve analysis showed that the TyG index (area under the ROC curve, AUC = 0.714) had superior predictive value compared with either glucose (AUC = 0.618) or TGs (AUC = 0.574) alone or their combination (AUC = 0.633). The optimal cut-off value for the TyG index was 8.795, with a sensitivity of 0.569 and a specificity of 0.753. A multivariate logistic regression analysis confirmed that the TyG index was independently associated with poor outcomes after adjusting for conventional prognostic factors. Adding the TyG index to a prediction model significantly improved its performance (AUC from 0.776 to 0.826, p = 0.032). Subgroup analyses revealed that the TyG index had enhanced prognostic value in elderly (≥65 years, AUC = 0.747) and male patients (AUC = 0.726).ConclusionElevated TyG index is independently associated with poor outcomes in patients with AIS after EVT. The TyG index demonstrates superior predictive performance compared to individual metabolic parameters and significantly improves outcome prediction when added to conventional prognostic factors. These findings suggest that the TyG index may serve as a valuable prognostic marker for risk stratification in patients with AIS undergoing EVT.